2016
DOI: 10.1038/srep27260
|View full text |Cite
|
Sign up to set email alerts
|

Hormetic Effect of Chronic Hypergravity in a Mouse Model of Allergic Asthma and Rhinitis

Abstract: We aimed to evaluate the effect of chronic hypergravity in a mouse model of allergic asthma and rhinitis. Forty BALB/c mice were divided as: group A (n = 10, control) sensitized and challenged with saline, group B (n = 10, asthma) challenged by intraperitoneal and intranasal ovalbumin (OVA) to induce allergic asthma and rhinitis, and groups C (n = 10, asthma/rotatory control) and D (n = 10, asthma/hypergravity) exposed to 4 weeks of rotation with normogravity (1G) or hypergravity (5G) during induction of asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…These findings are in line with our previously conducted studies. [ 10 ] Guéguinou et al reported that when animals were exposed to 2 G hypergravity for 3 weeks, serum IgG levels increased more than 2-fold, and IgA levels increased by 30%. [ 8 ] However, to the best of our literature review, it is the first time that we have observed changes in IgE levels of mice after their exposure to hypergravity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with our previously conducted studies. [ 10 ] Guéguinou et al reported that when animals were exposed to 2 G hypergravity for 3 weeks, serum IgG levels increased more than 2-fold, and IgA levels increased by 30%. [ 8 ] However, to the best of our literature review, it is the first time that we have observed changes in IgE levels of mice after their exposure to hypergravity.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we have shown that an appropriate degree of hypergravity could produce a hormetic effect on animals with allergic diseases. [ 10 ] However, whether this hormesis due to hypergravity is efficacious enough to be comparable to actual drug therapy has not been studied yet. Furthermore, no studies have been conducted to determine whether the anti-allergic effect of the combination of hypergravity and drug therapy on experimental animals with allergic diseases is greater than that of medication alone.…”
Section: Introductionmentioning
confidence: 99%
“…Increased gravitational force is commonly regarded to be harmful and noxious. However, several previous studies have shown that hypergravity has various beneficial effects on living organisms, such as enhancing the immune functions in mouse with allergic diseases, differentiation of the bone marrow mesenchymal stem cells into cardiac muscle and neuronal cells, and increasing the osteopontin expression in osteoblasts (Genchi et al, ; Jang, Jung, & Kim, ; Ling et al, ; Zhou, Zu, Sun, Zhuang, & Yang, ).…”
Section: Discussionmentioning
confidence: 99%
“…On day 21, pulmonary functions were determined, and after that, the rats were sacrificed under anesthesia using pentobarbital sodium (45 mg/kg, ip) after collection of blood samples and bronchoalveolar lavage fluids (BALF). The lung tissues were excised for the following biochemical assays [14,15].…”
Section: Experimental Protocols and Animal Model Preparationmentioning
confidence: 99%